Concept of Testing Process Maturity in Inter-organizational Networks - Aleksandra SUS; Michał ORGANA; Aleksandra KAWA (Communications of International Proceedings, 2021)
Regular monitoring of an organization in the context of process maturity allows it to reach its goals and identify opportunities and threats, which, as a result, may have a positive impact on its continuous improvement. There is a lot of research regarding process maturity in the subject literature, but is it possible to talk about process maturity in organizational networks at all? This study aims to identify the key dimensions of process maturity in technology clusters and, consequently, to develop the concept of a measurement tool in the entities mentioned. The result of this research is a developed research concept focusing on the synergy of two research approaches a) the CMMI model and b) a model identifying the process effectiveness of the network. The future implementation of the research will make it possible to verify the level of process maturity of the network on the example of a technology cluster, thus making a significant contribution to the development of science.
Keywords: Business process maturity; CMMI model; inter-organizational networks; technology claster